EXPRESSION OF THE STAPHYLOCOCCUS AUREUS LUKE GENE IN THE ESCHERICHIA COLI BL21(DE3) STRAIN - Abitayeva, G.K.; Bulanin, D.; Marchenko, E.V.; Vangelista, L. (Eurasian Journal of Applied Biotechnology, 2021)
Two-component leukotoxins are important virulence factors for Staphylococcus aureus. Despite efforts made to study S. aureus leukotoxins, the direct mechanism of action of these toxins during infection has not been determined. However, the observation that deletion of LukED significantly attenuates highly virulent S. aureus strains supports the hypothesis that selective inhibition of LukE / D may be useful in the development of new aspects of S. aureus infection control. For this purpose, this work was carried out to test the expression and obtain a recombinant form of the LukE protein in E.coli cells. The LukE gene was cloned into the pET28-c (+) / GFP vector containing the gfp gene. Two fused genes carrying a hexahistidine tag were expressed in cells of the E. coli BL21(DE3) strain. It was found that the 6His-GFP-LucE protein aggregates in inclusion bodies. 6His-GFP-LucE was washed out of inclusion bodies with high molar urea. The 6His-GFP-LucE protein was purified by metal affinity chromatography. Research results can be applied to obtain recombinant protein including strategies for inhibition of toxin activity.